Effect of 1-MCP on postharvest life of Lilium spp. foliar fertilized with calcium and boron - Rodríguez-Landero, Ana del Carmen; Franco-Mora, Omar; Morales-Rosales, Edgar Jesús; Pérez-López, Delfina de Jesús; Castañeda-Vildózola, Álvaro (Revista Mexicana de Ciencias Agrícolas, 2018)
Under greenhouse conditions, in Toluca, Mexico, 2009, in this research was studied the effect of foliar fertilization with calcium (Ca) and boron (B) on growth and shelf life of Lilium 'Nova Scotia'. Foliar fertilized with 43 mgL-1 CaOand15mgL-1 Bor130mgL-1 CaOand30 mg L-1 B, moreover, there was a control without foliar fertilization. After harvest was applied 0 or 500 nl L-1 of 1-methylcyclopropene (1-MCP), an ethylene antagonist, for 8 h in a sealed plastic container, and evaluated postharvest life. At harvest, generally, the content of Ca and B as well as of total sugars in the plant tissues was higher in plants with 130 mg L-1 CaO and 30 mg L-1 B or with 43 mg L-1 CaO and 15 mg L-1 B than control. The 1-MCP increased (p< 0.05) 2.5 days the vase life of stems foliar unfertilized; in stems treated with 43 mg L-1 CaO and 15 mg L-1 B, those with 1-MCP lasted up to 4.5 days more in comparison with untreated stems. While in stems treated with 130 mg L-1 CaO and 30 mg L-1 B no differences were found in vase life by effect of 1-MCP.
Keywords: Lilium ‘Nova Scotia’; flower quality; nutrition; senescence